On the issue of the population's attitude towards vaccinations and medical exemptions - Oksana V. Moskalets (LLC "MEDIAFORMAT", 2024)
Background. Despite the enormous successes that have been achieved in the fight against infectious diseases thanks to mass preventive vaccination, primarily the reduction of child mortality, anti-vaccination sentiment continues to spread among the population. One of the reasons is the unjustified medical exemptions from vaccinations, which were widely used in the past, and the shortcomings of taking into account adverse events after immunization. Aim. Analysis of the grounds for medical objections to vaccination and the attitude of the population towards it. Methods. A retrospective analysis of clinical and anamnestic data and the results of a survey of 108 adult patients referred for consultation with an allergist-immunologist to decide on the possibility of carrying out specific immunoprophylaxis was carried out. Results. Previously issued medical exemptions from vaccinations were given to 92 patients (85%), with 53 patients (57.6%) based on intolerance to various drugs and only 14 (15.2%) due to adverse events after immunization, however, there was documentary evidence in only 2 patients. In 75 cases (68.5%) various allergic diseases were recorded, for which 27.2% of patients also received medical exemptions. After consultation, only 11 (10.2%) individuals had temporary contraindications against vaccination and 1 absolute contraindication (against ADS-M). The survey data showed that 38 respondents (35.1%) were confident that they would definitely develop an allergic reaction to the vaccine, 6 (6.2%) did not trust any vaccines, and another 9 people. (9.3%) were apprehensive because for one reason or another, they received a medical exemption in early childhood or their parents did not previously consent to vaccination. The main reasons for mistrust (using the example of SARS-CoV-2): fear of side effects (88.6%). insufficient knowledge (56.7%), low efficiency (43.8%), excess profits of pharmaceutical companies (35%), opinion of medical workers (24.7%), mandatory nature of vaccination (27.8%). Conclusion. Unreasonable medical exemptions from vaccination, including in patients with allergic diseases, as well as the lack of appropriate medical documentation create a big problem for an objective assessment of the possibility of carrying out specific immunoprophylaxis in a particular patient. Anti-vaccination sentiments in society are quite widespread and often medical workers have a direct connection to this.